2019
DOI: 10.3390/nano9091237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Femtosecond Laser Surface Nanotexturing on the Friction Behavior of Silicon Sliding Against PTFE

Abstract: The aim of the present work was to investigate the influence of laser-induced periodic surface structures (LIPSS) produced by femtosecond laser on the friction behavior of silicon sliding on polytetrafluoroethylene (PTFE) in unlubricated conditions. Tribological tests were performed on polished and textured samples in air using a ball-on-flat nanotribometer, in order to evaluate the friction coefficient of polished and textured silicon samples, parallel and perpendicularly to the LIPSS orientation. In the poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Most of these employed hard textured substrates such as stainless steel [179][180][181][182][183], bronze [184][185][186], silicon [187] or laminated ceramics [188,189], which were rubbing against an untextured PTFE nano-composite. Surface textures were mainly produced by LST using lasers with pulse durations ranging from micro- [179,181,[184][185][186] and nano- [188,189] to pico- [182] and femtoseconds [180,187]. Regarding the geometry of the textures, research effort has focused on dimples [179, 181-183, 185, 186, 188, 189], unidirectional grooves [180], grid-like textures, and circumferentially or radially aligned grooves [184].…”
Section: Ptfe and Surface Texturesmentioning
confidence: 99%
“…Most of these employed hard textured substrates such as stainless steel [179][180][181][182][183], bronze [184][185][186], silicon [187] or laminated ceramics [188,189], which were rubbing against an untextured PTFE nano-composite. Surface textures were mainly produced by LST using lasers with pulse durations ranging from micro- [179,181,[184][185][186] and nano- [188,189] to pico- [182] and femtoseconds [180,187]. Regarding the geometry of the textures, research effort has focused on dimples [179, 181-183, 185, 186, 188, 189], unidirectional grooves [180], grid-like textures, and circumferentially or radially aligned grooves [184].…”
Section: Ptfe and Surface Texturesmentioning
confidence: 99%
“…For instance, Chowdhury et al [ 9 ] studied the effect of normal load and sliding velocity on the tribological properties of aluminum using a pin-on-disc test; the results showed that the friction coefficient decreases when the normal load or the velocity increases, whereas the wear rate exhibits an opposite dependence on the normal load and sliding velocity. More experiments were performed to study the friction and wear under different conditions, including incidence angle [ 10 ], crystal orientation [ 11 , 12 ], coatings or oxidation [ 13 , 14 , 15 ], and surface texture [ 16 , 17 ]. In addition, the tribochemical reactions [ 18 ] at the sliding interface may also affect the material properties such as interfacial adhesion and material plasticity, resulting in the variation of frictional and wear processes.…”
Section: Introductionmentioning
confidence: 99%
“…Laser patterning can be a powerful technique for high-resolution surface nano-engineering [ 9 , 10 , 11 , 12 ]. It is a non-contact, mask-less, and flexible/versatile method with direct generation of micro- and nano-structures called laser-induced periodic surface structures (LIPSSs) observed on a wide range of materials, such as semiconductors [ 13 , 14 ], metals and alloys [ 15 , 16 , 17 , 18 , 19 ], metal oxides [ 20 , 21 , 22 , 23 ], inorganic compounds [ 24 , 25 ], and polymers [ 26 ]. Micro- and nano-structures could also be simultaneously observed in hierarchical patterns [ 19 , 24 ].…”
Section: Introductionmentioning
confidence: 99%